Therapeutic Exosomes in Prognosis and Developments of Coronary Artery Disease - Chen, Ai-Qun; Gao, Xiao-Fei; Wang, Zhi-Mei; Wang, Feng; Luo, Shuai; Gu, Yue; Zhang, Jun-Jie; Chen, Shao-Liang (Frontiers in Cardiovascular Medicine, 2021)
Exosomes, with an diameter of 30 150 nm, could be released from almost all types of cells, which contain diverse effective constituent, such as RNAs, proteins, lipids, and so on. In recent years, exosomes have been verified to play an important role in mechanism, diagnosis, treatment, and prognosis of cardiovascular disease, especially coronary artery disease (CAD). Moreover, it has also been shown that exosomes derived from different cell types have various biological functions based on the cell stimulation and microenvironment. However, therapeutic exosomes are currently far away from clinical translation, despite it is full of hope. In this review, we summarize an update of the recent studies and systematic knowledge of therapeutic exosomes in atherosclerosis, myocardial infarction, and in-stent restenosis, which might provide a novel insight into the treatment of CAD and promote the potential clinical application of therapeutic exosomes.